2016
DOI: 10.1002/jcph.857
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hepatic Impairment Does Not Affect Doravirine Pharmacokinetics

Abstract: Doravirine is a novel, potent, nonnucleoside reverse-transcriptase inhibitor currently in development for HIV-1 infection treatment. As a substrate for CYP3A-mediated metabolism, doravirine could potentially be affected by liver-function changes. As a portion of the HIV-1-infected population has varying degrees of liver impairment, we investigated the effect of moderate hepatic impairment on the pharmacokinetic profile and tolerability of single-dose doravirine 100 mg in otherwise healthy subjects. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…The decrease in olaparib absorption could counteract the theoretical effect of decreased metabolism, resulting in little change in the net exposure to olaparib in patients with moderate hepatic impairment compared with those with normal hepatic function. In addition, it has also been reported that there is a lack of effect of moderate hepatic impairment on the PK of substrates that are largely cleared by CYP3A 25,26 . Taken together, the results of the current study and those previously reported suggest that mild or moderate hepatic impairment will have no clinically significant effect on exposure to olaparib.…”
Section: Discussionsupporting
confidence: 76%
“…The decrease in olaparib absorption could counteract the theoretical effect of decreased metabolism, resulting in little change in the net exposure to olaparib in patients with moderate hepatic impairment compared with those with normal hepatic function. In addition, it has also been reported that there is a lack of effect of moderate hepatic impairment on the PK of substrates that are largely cleared by CYP3A 25,26 . Taken together, the results of the current study and those previously reported suggest that mild or moderate hepatic impairment will have no clinically significant effect on exposure to olaparib.…”
Section: Discussionsupporting
confidence: 76%
“…Steady-state AUC was selected as the exposure measure from which to judge clinical relevance from a safety perspective, as this parameter is an integration of concentrations over the 24-h dosing interval in which individuals are exposed to doravirine at steady state. In phase I trials, there was no evidence that the incidence of overall AEs or specific AEs was temporally associated with doravirine T max [11,15,[20][21][22][23][24][25][26][27][28][29][30][31], therefore suggesting that C max does not play a major role in safety or tolerability. In the phase IIb trial, there was no evidence of exposure-or dose-related toxicities across the range of 25-200 mg doses evaluated, and no meaningful association between doravirine steady-state exposure and the incidence of neuropsychiatric AEs or fasting lipid levels that would further limit the exposure of doravirine from a safety perspective [17].…”
Section: Definition Of the Bounds Of Clinical Relevancementioning
confidence: 98%
“…The effects of demographic factors including age, gender, hepatic impairment, and renal impairment on doravirine pharmacokinetics were evaluated in dedicated phase I trials in participants without HIV-1 infection [22,24,25]. In addition, a population pharmacokinetic analysis of individuals with (n = 959) and without (n = 341) HIV-1 infection was conducted across the phase I, II, and III trials to evaluate the effects of these factors-as well as body weight, body mass index (BMI), race, or ethnicity-on doravirine pharmacokinetics [14].…”
Section: Effect Of Demographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations